dampak Dampak penerapan prinsip syariah terhadap loyalitas konsumen pada Koperasi Rohmatul Ummah - Azhari, Muhammad (Jurnal Riset Ekonomi dan Bisnis Mahasiswa : Brainy, 2025)
This study aims to analyze the impact of the implementation of sharia principles in the Rohmatul Ummah cooperative on consumer loyalty in a modern business context. As public awareness of the importance of ethics, social responsibility, and sustainability in business practices increases, sharia values, including justice ('adl), goodness (ihsan), transparency (tabligh), and professionalism (fathanah), are becoming increasingly relevant. These principles govern not only financial aspects but also encompass all business activities, such as production, distribution, and marketing. This study uses a qualitative approach with a literature review and conceptual analysis to explore the relationship between the implementation of sharia principles and levels of consumer loyalty. The results indicate that consistent application of sharia principles can increase consumer trust, which in turn strengthens emotional and spiritual attachment to the brand. Consumer loyalty is formed not only based on product or service quality but also due to perceptions of moral integrity and the blessings of transactions carried out. These findings provide important implications for companies, both sharia-based and conventional, to integrate ethical values into customer management strategies to build sustainable loyalty.